The Life and Scientific Legacy of Indonesian Paleontologist Dr. Tan Sin Hok (1902-1945) - Munasri Munasri; J.T. (Han) van Gorsel (Berita Sedimentologi, 2014)
Tan Sin Hok was probably Indonesia's most influential paleontologist. He was born and raised in West Java and was the only Indonesian with an academic earth science education from The Netherlands before World War II. His Ph.D thesis in 1927 was a pioneering study on little-known Cretaceous radiolaria and Tertiary calcareous nannofossils from Roti and Timor. Subsequent work during his professional career as paleontologist of the Geological Survey in Bandung mainly focused on evolution of Cenozoic larger foraminifera. Tan's scientific legacy was accomplished before he was 40 years old, when the Japanese occupation terminated his research and the turmoil immediately thereafter took his life.Although Tan Sin Hok made significant original contributions to taxonomy and evolution of several microfossil groups, he initially failed to recognize the potential biostratigraphic value of radiolaria and nannofossils; important high-resolution zonations of these groups were developed by other workers in the 1950's and later. Tan's novel approach to evolution and systematics of larger foraminifera of Indonesia appeared to resonate only with 'schools' in The Netherlands, probably largely because his publications were mainly written in Dutch and German and published in Dutch and 'Netherlands Indies' journals with limited distributions.